The inflammatory spectrum of cardiomyopathies - Musigk, Nicolas; Suwalski, Phillip; Golpour, Ainoosh; Fairweather, DeLisa; Klingel, Karin; Martin, Pilar; Frustaci, Andrea; Cooper, Leslie T.; Lüscher, Thomas F.; Landmesser, Ulf; Heidecker, Bettina (Frontiers in Cardiovascular Medicine, 2024)
Infiltration of the myocardium with various cell types, cytokines and chemokines plays a crucial role in the pathogenesis of cardiomyopathies including inflammatory cardiomyopathies and myocarditis. A more comprehensive understanding of the precise immune mechanisms involved in acute and chronic myocarditis is essential to develop novel therapeutic approaches. This review offers a comprehensive overview of the current knowledge of the immune landscape in cardiomyopathies based on etiology. It identifies gaps in our knowledge about cardiac inflammation and emphasizes the need for new translational approaches to improve our understanding thus enabling development of novel early detection methods and more effective treatments.